The effectiveness of study, explore, implement, evaluate model e-learning based on project-based learning on the conceptual understanding and agility of students - Komang Setemen; I Gede Sudirtha; I Wayan Widiana (OmniaScience, 2023)
The results of online learning were not optimal, as evidenced by the unsatisfactory learning outcomes. These issues influenced students who had a poor understanding of concepts and those who were quick to learn. It was the reason for the study that aims to analyze the effectiveness of study, explore, implement, evaluate (SEIE) model e-learning based on project-based learning (PjBL) on the conceptual understanding and agility of students. The research design is a posttest control group design, which is a quasi-experimental design. The sample size for this study is 58 students, including 28 in the experimental group and 30 in the control group. The study used test and questionnaire methods to collect research data. A test instrument in the form of a description of 10 questions was used to assess conceptual understanding, and a questionnaire instrument with 30 statements was used to assess their agility. Quantitative descriptive analysis and inferential statistical analysis using MANOVA were utilized as data analysis methods and techniques. The findings revealed that the SEIE model e-learning based on PjBL was beneficial in improving students' ability to understand concepts and their agility as learners, both partially and simultaneously. This condition was indicated by the value of sig. < 0.05. As a result, the SEIE model e-learning based on PjBL was effective on students' ability to understand concepts and their agility, both partially and simultaneously. Thus, this model became a learning recommendation for improving conceptual understanding and agility.